Identification of Microplastics in Common Carp (Cyprinus carpio) at Koto Panjang Reservoir Kampar Regency Riau Province - Ulfa, Dwi Astria; Purwanto, Eko; Budijono, Budijono (Jurnal Perikanan dan Kelautan, 2022)
In the Koto Panjang Reservoir, the microplastic may originate from the degraded plastic waste as well as degraded plastic net from the fish culturing cages. The microplastic may be accidentally ingulfed as fish swallowing their food. To understand the presence of microplastic present in the stomach of wild common carps living around the fish net cage, a study was conducted in December 2020-February 2021. The fish were captured using fish net (3-5 inc mesh size), 3 times, once/ 2 weeks. The fish stomach was removed and the presence of the microplastic was identified. The stomach content of the fish was mixed with 10% KOH (minimum 3 x of stomach content volume) and was incubated for2 weeks to dilute the organic materials. Then the presence of microplastic was observed using a binocular microscope. Types and abundance of the microplastic was noted. Results shown that the types of microplastic present were films, fibers and fragments. The highest type of microplastic found in the stomach of the fish was films (2.3 particles/ fish), followed by fibers (0.6 particles/fish) and fragments (1.1 particles/ fish).